The Effect of Marketing Mix, Perception and Consumers’ Knowledge on NEUROAID Buying Decision at South Sumatera Region - Quadrianti, Lilly; Asiati , Diah Isnaini; Nurrahmi, Maftuhah (International Journal of Marketing & Human Resource Research, 2024)
This research aims to determine the influence of the marketing mix (product, price, place, promotion) and consumer perception and knowledge on purchasing decisions for Neuroaid in the Southern Sumatra region. The type of research is descriptive research with a quantitative approach. This research uses independent variables, namely marketing mix (product, price, place, promotion) and perception and knowledge, and the dependent variable is purchasing decisions. The population is consumers of Neuroaid PT. Mersifarma, southern Sumatra, with a sample of 92 people taken using cluster sampling. The data used is primary data with a questionnaire data collection method. The analysis technique used by researchers is Multiple Linear Regression. The research results prove that simultaneously 1) There is a positive and significant influence of the marketing mix (product, price, place, promotion) and perception and knowledge on purchasing decisions; 2) There is a positive and significant influence of the product on purchasing decisions; 3) There is a positive and significant influence of price on purchasing decisions; 4) There is a positive and significant influence of place on purchasing decisions; 5) There is a positive and significant influence of promotion on purchasing decisions; 6) There is a positive and significant influence of perception on purchasing decisions; 7) There is a positive and significant influence of knowledge on purchasing decisions.